2009
DOI: 10.1111/j.1365-3164.2008.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of allergen‐specific immunotherapy in human and veterinary medicine

Abstract: This article reviews allergen-specific immunotherapy in human and veterinary medicine. Current hypotheses of possible mechanisms of actions are outlined. Indications, success rates, adverse effects and factors influencing outcome of therapy are discussed in humans, dogs, cats and horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
104
2
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 178 publications
(259 reference statements)
10
104
2
8
Order By: Relevance
“…Studies evaluating the efficiency of AIT found that 52–65 per cent of the treated dogs show a clinical improvement of at least 50 per cent (Zur and others 2002, Schnabl and others 2006, Loewenstein and Mueller 2009). In a prospective blinded study evaluating AIT, improvement of CADESI scores and pruritus of at least 50 per cent was reported in 7/11 dogs (64 per cent) and in 5/11 dogs (45 per cent), respectively (Mueller and others 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating the efficiency of AIT found that 52–65 per cent of the treated dogs show a clinical improvement of at least 50 per cent (Zur and others 2002, Schnabl and others 2006, Loewenstein and Mueller 2009). In a prospective blinded study evaluating AIT, improvement of CADESI scores and pruritus of at least 50 per cent was reported in 7/11 dogs (64 per cent) and in 5/11 dogs (45 per cent), respectively (Mueller and others 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic reactions have been reported in approximately 1 per cent of the treated dogs (Angorano and MacDonald 1991). They include not only gastrointestinal signs, but also weakness, anxiety, urticaria/angio-oedema and severe reactions such as collapse and anaphylaxis (Rosser 1998, Scott and others 2001, Loewenstein and Mueller 2009). None of the latter ones could be observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoidance of offending allergens is often not possible in this disease. Allergen-specific immunotherapy takes months to optimal effect (Mueller and Bettenay 1996), and in many cases will still require additional symptomatic therapy (Loewenstein and Mueller 2009). As atopic dermatitis typically requires life-long management, treatments with infrequent and mild clinical adverse effects are preferred.…”
Section: Discussionmentioning
confidence: 99%
“…The only specific treatment for atopic dermatitis is allergen-specific immunotherapy (Mueller and Bettenay 1996, Olivry and Sousa 2001a, Loewenstein and Mueller 2009). Symptomatic treatment includes a number of options, such as glucocorticoids (Olivry and Sousa 2001b), cyclosporine (Steffan and others 2006), shampoos (Löflath and others 2007), essential fatty acids (Mueller and others 2004, Olivry and others 2010a, b) and antihistamines (DeBoer and Griffin 2001, Olivry and Mueller 2003).…”
Section: Introductionmentioning
confidence: 99%